2009
DOI: 10.1080/13284200802702056
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of intolerance of uncertainty treatment for anxiety disorders

Abstract: Intolerance of uncertainty (IU) is the tendency to react negatively to uncertain situations or events, and it has been found to be an important maintaining factor in a number of different anxiety disorders. It is often included as a part of cognitive behavioural interventions for anxiety disorders but its specific contribution to treatment outcome has not been examined.The aim of the present study was to examine the effectiveness of a brief treatment specifically targeting IU in a 25-year-old man with comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…These results are consistent with previous research supporting the effectiveness of CBGT for social phobia (McEvoy, 2007), as well as findings which demonstrate that IU reduces during cognitive behavior therapy for anxiety disorders such as GAD and OCD (Belloch et al, 2011;Goldman et al, 2007;Overton & Menzies, 2005). Our treatment outcomes also appear consistent with those reported in Hewitt et al's (2009) single-case study that found that an IU-based CBT intervention led to clinically significant reductions in IU and social phobia symptoms. The primary focus of the intervention in the Hewitt et al study was to reduce IU via cognitive and behavioral strategies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with previous research supporting the effectiveness of CBGT for social phobia (McEvoy, 2007), as well as findings which demonstrate that IU reduces during cognitive behavior therapy for anxiety disorders such as GAD and OCD (Belloch et al, 2011;Goldman et al, 2007;Overton & Menzies, 2005). Our treatment outcomes also appear consistent with those reported in Hewitt et al's (2009) single-case study that found that an IU-based CBT intervention led to clinically significant reductions in IU and social phobia symptoms. The primary focus of the intervention in the Hewitt et al study was to reduce IU via cognitive and behavioral strategies.…”
Section: Discussionsupporting
confidence: 94%
“…One study to date has explored IU within the context of social phobia treatment. In a single-case design series, Hewitt, Egan, and Rees (2009) found that an IU-based intervention significantly reduced social anxiety symptoms for a man with comorbid diagnoses of social phobia, panic disorder, generalized anxiety disorder, major depressive disorder, and dysthymia. IU also reduced following treatment, but the single-case design limits conclusions about (a) the relationship between improvements in IU and reductions in social phobia symptoms, and (b) the generalizability of these relationships.…”
Section: Introductionmentioning
confidence: 98%
“…This finding runs parallel with the previous studies of Hewitt et al (2009);Krohne (1993); Dugas et al (1997); Lee et al (2010); and Nuevo et al (2009). According to Basevitz et al (2008), elderly people had less intolerance of uncertainty and less belief in the functional value of worrying compared to younger adults.…”
Section: Discussionsupporting
confidence: 93%
“…However, Graham (2003) and D'Hudson and Saling (2010), for their part, persisted that worry is a distinguishable construct to elderly. Hewitt, Egan, and Rees (2009) and Krohne (1993) suggested that IU may motivate a number of behaviors and cognitions such as worry. Dugas et al (1997) proposed that worry is a mental reaction to uncertainty.…”
Section: Worrymentioning
confidence: 98%
“…Research has also examined other cognitive-behavioral interventions that do not specifically target IU, but nonetheless have shown a reduction in IU and symptoms of social anxiety (Hewitt, Egan, & Rees, 2009;Mahoney & McEvoy, 2012b), health anxiety (Langlois & Ladouceur, 2004), anxiety and depressive disorders (Bomyea et al, 2015), delivered as individual and group transdiagnostic interventions (Boswell et al, 2013; Abramowitz and Arch (2014) made a compelling argument that exposure-driven cognitive-behavioral treatment for obsessive-compulsive disorder may benefit from strengthening inhibitory learning of nonthreatening associations (e.g., uncertainty is intolerable), such that uncertainty becomes increasingly acceptable as normal across contexts. Abramowitz and Arch (2014) suggest treatment should emphasize tolerating uncertainty through exposure, which may strengthen inhibitory associations.…”
Section: What Is Known?mentioning
confidence: 99%